Mastery learning: it is time for medical education to join the 21st century - McGaghie, William C (Academic medicine, 2015)
Clinical medical education in the 21st century is grounded in a 19th-century model that relies on longitudinal exposure to patients as the curriculum focus. The assumption is that medical students and postgraduate residents will learn from experience, that vicarious or direct involvement in patient care is the best teacher. The weight of evidence shows, however, that results from such traditional clinical education are uneven at best. Educational inertia endorsed until recently by medical school accreditation policies has maintained the clinical medical education status quo for decades.Mastery learning is a new paradigm for medical education. Basic principles of mastery learning are that educational excellence is expected and can be achieved by all learners and that little or no variation in measured outcomes will result. This Commentary describes the origins of mastery learning and presents its essential features. The Commentary then introduces the eight reports that comprise the mastery learning cluster for this issue of Academic Medicine. The reports are intended to help medical educators recognize advantages of the mastery model and begin to implement mastery learning at their own institutions. The Commentary concludes with brief statements about future directions for mastery learning program development and research in medical education.